2012
DOI: 10.1021/ol3025082
|View full text |Cite
|
Sign up to set email alerts
|

Base-Mediated Carboxylation of Unprotected Indole Derivatives with Carbon Dioxide

Abstract: A simple and straightforward method for the preparation of indole-3-carboxylic acids was discovered through the direct carboxylation of indoles with atmospheric pressure of carbon dioxide (CO(2)) under basic conditions. The key for the reaction was found to be the use of a large excess of LiO(t)Bu as a base to suppress the undesired decarboxylation side reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(47 citation statements)
references
References 41 publications
(12 reference statements)
0
44
1
1
Order By: Relevance
“…图 3 叔丁醇锂作用下的吲哚 3 位羧基化反应 [5] Figure 3 Direct carboxylation of indole mediated by LiOBu-t [5] 碱在溶液中的状态也会影响反应的结果. 刘磊等 [6] 为解决反应中无机碱在有机溶剂中的溶解度不好的问 题, 设计合成了离子型有机碱(由大位阻有机阳离子和 碱性阴离子组成, 如图 4 所示).…”
Section: Figureunclassified
“…图 3 叔丁醇锂作用下的吲哚 3 位羧基化反应 [5] Figure 3 Direct carboxylation of indole mediated by LiOBu-t [5] 碱在溶液中的状态也会影响反应的结果. 刘磊等 [6] 为解决反应中无机碱在有机溶剂中的溶解度不好的问 题, 设计合成了离子型有机碱(由大位阻有机阳离子和 碱性阴离子组成, 如图 4 所示).…”
Section: Figureunclassified
“…In 2012, the Kobayashi group found that LiO t Bu allowed the formation of indole‐3‐carboxylic acid derivatives under ambient CO 2 atmosphere 15. Interestingly, the authors found the use of a large excess of LiO t Bu (5 equiv) was essential to prevent competing product decarboxylation and to improve yields and reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…(Scheme 60) [140]. Under optimized conditions (ambient CO2 pressure, 100 °C) the use of a large excess of LiO t Bu was found (5 eq.)…”
Section: Base-promoted Carboxylation Of Aromatic and Heteroaromatic Cmentioning
confidence: 96%